Serology with ML Flow test in health professionals from three different states of Brazil - Karla Lucena Sampaio Calado; Mônica Maria Ferreira Magnanini; Rodrigo Scaliante de Moura; Maria Eugenia Noviski Gallo; Samira Bührer-Sékula; Maria Leide Wand- (Sociedade Brasileira de Dermatologia, 2013)
BACKGROUND: In highly endemic countries, transmission and sub-clinical infection of leprosy are likely and the disease manifests itself in individuals without any known close contact with a leprosy patient. Health workers are social contacts belonging to the same network (the Health System) and some of them share the same social environment (nursing assistants) as patients with known patients and / or carriers. OBJECTIVE: To identify ML Flow seropositivity among health professionals. METHODS: We conducted a cross-sectional study using a serological survey with the ML Flow test in 450 health professionals (doctors, nurses and nursing assistants), in order to detect seropositivity in areas of high and low endemicity in municipalities from three Brazilian states (RJ, MS and RS). RESULTS: The results showed general 16% seropositivity, higher in low endemic areas, regardless of whether there was direct care for leprosy patients. Paradoxically, a statistical association was observed between the area studied and seropositivity, as the place with the lowest endemicity (CA) had the highest seropositivity rate (p = 0.033). CONCLUSION: The authors suggest these results are associated with a presence of an unspecified link to bovine serum albumin (BSA), carrier of PGL-1 in the ML Flow test, and recommend expanded seroepidemiological research utilizing tests with human and bovine albumin.